Импульсно-пучковая обработка промышленно-бытовых сточных вод; Известия вузов. Физика; Т. 56, № 7-2 - Ремнев Г. Е. Геннадий Ефимович; Кайканов М. И. Марат Исламбекович; Степанов А. В. Андрей Владимирович; Сазонов Р. В. Роман Владимирович; Меринова Л. Р. Лилия Рашидовна; Егоров И. С. Иван Сергеевич; Колоколов Д. Ю. Дмитрий Юрьевич (2013, 2013)
Заглавие с экрана